Evaluation of different plate media for direct cultivation of Campylobacter species from live broilers - Potturi-Venkata, Lakshmi Prasanna; Backert, Steffen; Lastovica, A. J.; Vieira, Sergio; Norton, Robert A.; Miller, Robert S.; Pierce, S. J.; Oyarzabal, Omar A. (Poultry Science, 2007)
Accurate identification and optimal culturing procedures for Campylobacter spp. from live broilers are needed for epidemiological studies. Because there is no standardized protocol, we designed and conducted studies to evaluate different selective media for the culturing and isolation of Campylobacter spp. from cecal and fecal samples obtained from battery-reared and commercial broilers. Five media selective for Campylobacter were evaluated: Campylobacter agar base, Campylobacter, Campy-Line, modified Campy-Cefex, and modified charcoal cefoperazone deoxycholate agar. With contaminated broilers reared in battery cages, Campylobacter agar base, Campylobacter, modified Campy-Cefex, and modified charcoal cefoperazone deoxycholate agar revealed similar isolation rates (P > 0.05), whereas Campy-Line showed a lower efficacy (P < 0.05). With commercial live broilers, modified Campy-Cefex agar was more consistent for the isolation of Campylobacter from feces, whereas modified Campy-Cefex and modified charcoal cefoperazone deoxycholate agar showed similar isolation rates from cecal samples. Campy-Line agar showed a lower identification rate (P < 0.05) for both fecal and cecal samples. A multiplex PCR assay used for identification showed that Campylobacter jejuni and Campylobacter coli DNA was present in the samples. Pulsed field gel electrophoresis restriction profiles differed among samples collected from different commercial farms but were similar for isolates from the same farm, suggesting clonal differences. No variation was seen in pulsed field gel electrophoresis patterns among isolates cultured on different media. Our data suggest that the choice of plate medium may influence the efficiency of isolating Campylobacter spp. from broiler chickens by direct plating from fecal or cecal samples. ©2007 Poultry Science Association Inc.
Created from Fastlane, Scopus look-up
Keywords: Broiler; Campylobacter; Plate media